Polydopamine-Derived Carbon: What a Critical Role for Lithium Storage? - Qian, Xiaoyong; Zhang, Fangzhou; Zhao, Yuye; Liang, Kai; Luo, Wei; Yang, Jianping (Frontiers in Energy Research, 2020)
Polydopamine-derived carbon materials has attracted tremendous attention owing to nitrogen heteroatoms dope. However, it is challenging to evaluate the effect of the morphology and porosity of the polydopamine-derived carbon for lithium storage.Here, we designed three polydopamine-derived carbon materials with different morphologies and porosity: carbon nanospheres (CNs), mesoporous carbon nanospheres (MCNs), bowl-like mesoporous carbon nanoparticles (BMCNs) to evaluate the electrochemical performance. Such a bowl-like mesoporous structure combines multiple advantageous features, including mesoporous channels and shorter transmission distance, thus delivers a high specific capacity. In addition, our work provides a new insight into the electrochemical performance of polydopamine-derived carbon and a useful reference for its future application in high-performance lithium ion batteries electrode materials.